Caring for Computers: The Hidden Work of Clinical Nurses during the Introduction of Health Information Systems in a Teaching Hospital in Taiwan - Feng-Tzu Huang (MDPI AG, 2021)
Implementing health information systems for enhancing patient care and management occurs worldwide. Discovering how nurses, as important system end-users, experience technology-reliant clinical practice involved focus groups (n = 25) and in-depth individual interviews with nurses (n = 4) and informatics staff (n = 3) in a major Taiwanese medical center. This qualitative study explores the unintended effects of these systems on nurses' role and clinical practice. First, nurses' additional role caring for computer devices supporting patient care involves highly-demanding invisible effort, especially when tackling system malfunctions affecting patients with urgent conditions. Second, nurses are resourceful in developing solutions to protect patients during unexpected technical malfunctions. Third, troubleshooting using telephone technical support as the first resort is problematic. It is argued that computerization requires nurses to care for co-clients: patients and computers. Managing technical malfunctions is an unintended consequence for nurses, reflecting the hidden work required by new technology.